Patellar Tendon Stiffness Is Not Reduced During Pregnancy - Bey, Marie Elena; Marzilger, Robert; Hinkson, Larry; Arampatzis, Adamantios; Legerlotz, Kirsten (Frontiers in Physiology, 2019)
It is believed that hormonal changes during pregnancy lead to an increased compliance in ligaments and tendons, increasing the risk to suffer from connective tissue injuries particularly during exercise. While the laxity of the pelvic ligaments may increase to facilitate childbirth, to our knowledge no study has ever investigated the mechanical properties of human tendons in different stages of pregnancy. Thus, the purpose of our longitudinal study was to investigate the mechanical properties of the patellar tendon in different stages of pregnancy and postpartum. Nineteen pregnant women (30±4 years) and eleven non-pregnant controls (28±3 years) performed maximum isometric knee extension contractions on a dynamometer. Muscle strength and mechanical properties of the patellar tendon were determined integrating ultrasound, kinematic and electromyographic measurements. In pregnant women, measurements were performed in the 16±4th week of pregnancy (EP), the 29±4th week of pregnancy (LP) and 32±9th weeks postpartum (PP). On average, muscle strength as well as patellar tendon stiffness, force and relative strain did not change during pregnancy and did not differ from non-pregnant controls. Tendon length measured at 90° knee flexion continuously increased during and after pregnancy (tendon length PP>EP; PP>controls). Our results indicate that patellar tendon stiffness is not universally affected by pregnancy. We found no evidence to support the often stated assumption that tendons would become more compliant during pregnancy. However, variability between individuals as well as the progressive increase in tendon rest length during and after pregnancy and its implications on injury risk need to be further examined.